Research and development of virtualization in Wireless sensor networks - M. Sandeep Kumar; Prabhu. J (Politeknik Negeri Padang, 2018)
Virtualization is foundational for applying both cloud computing and big data. It provides the basis for many platform attributes required to access, store, analyze, and manage the distributed computing components in big data environments. Virtualization also able to use in a wireless sensor network in Agriculture field. WSNs emerging approach in commercial applications like Healthcare, agriculture, Industries. Virtualization in sensor network offers more flexibility, cost, effective solution; promote diversity, security, and manageability. In this chapter describes WSNs in agriculture domain, issues, challenges, etc. Also describes virtualization technology, techniques, and tools.